2020
DOI: 10.1007/s00384-020-03757-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers detected in blood, stool, urine, and tissue in colorectal cancer: a systematic review of paired samples

Abstract: Purpose Methylated cell-free DNA in liquid biopsies are promising non-invasive biomarkers for colorectal cancer (CRC). Optimal markers would have high sensitivity and specificity for early detection of CRC and could be detected in more than one type of material from the patient. We systematically reviewed the literature on DNA methylation markers of colorectal cancer, detected in more than one type of material, regarding their potential as contributors to a panel for screening and follow-up of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…Saliva, urines, seminal fluids, tears, and stool have been analyzed to understand their correlation with cancer 36 . Stool in particular have been thoroughly evaluated in the context of gastrointestinal cancers, and proved to be a valuable source of tumoral DNA for pancreatic cancer [37][38][39][40] . Stool analysis from a multiomics perspective is also able to integrate information on the role of the microbiome in cancer pathogenesis, especially in the case of colorectal cancer and pancreatic cancer, as well as in other disease entities such as inflammatory intestinal diseases [41][42][43] .…”
Section: Liquid Biopsies In Cancermentioning
confidence: 99%
“…Saliva, urines, seminal fluids, tears, and stool have been analyzed to understand their correlation with cancer 36 . Stool in particular have been thoroughly evaluated in the context of gastrointestinal cancers, and proved to be a valuable source of tumoral DNA for pancreatic cancer [37][38][39][40] . Stool analysis from a multiomics perspective is also able to integrate information on the role of the microbiome in cancer pathogenesis, especially in the case of colorectal cancer and pancreatic cancer, as well as in other disease entities such as inflammatory intestinal diseases [41][42][43] .…”
Section: Liquid Biopsies In Cancermentioning
confidence: 99%
“…DNA methylation is one of the most important and earliest epigenetic hallmarks of CRC [ 133 ]. Up to now, clinical studies have shown that the methylated epigenetic ctDNA markers serve as promising candidates for CRC screening modality in serum/plasma of CRC patients [ 134 ]. A study by Young et al, designed a multi-panel methylation assay for detection of specific methylation markers, Branched Chain Amino Acid Transaminase 1(BCAT1), IKAROS Family Zinc Finger 1I(KZF1) and Interferon Regulatory Factor 4 (IRF4), in plasma of CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of cancer diagnostics, non-invasive technologies are increasingly attractive for initial diagnosis of tumors and for therapy monitoring [1][2][3]. Body fluids are the primary source of liquid biopsy, i.e., biomarker detection, and include blood and serum, urine, and saliva [4,5].…”
Section: Introductionmentioning
confidence: 99%